Invasion, isolation and evolution shape population genetic structure in Campanula rotundifolia. Issue 2 (12th March 2020) - Wilson, Julia; Perry, Annika; Shepherd, Jessica R; Durán-Castillo, Mario; Jeffree, Christopher E; Cavers, Stephen
Abstract: The distribution and genetic structure of most plant species in Britain and Ireland bear the imprint of the last ice age. These patterns were largely shaped by random processes during recolonization but, in angiosperms, whole-genome duplication may also have been important. We investigate the distribution of cytotypes of Campanula rotundifolia, considering DNA variation, postglacial colonization, environmental partitioning and reproductive barriers. Cytotypes and genome size variation from across the species' range were determined by flow cytometry and genetic variation was assessed using cpDNA markers. A common garden study examined growth and flowering phenology of tetraploid, pentaploid and hexaploid cytotypes and simulated a contact zone for investigation of reproductive barriers. Irish populations were entirely hexaploid. In Britain, hexaploids occurred mostly in western coastal populations which were allopatric with tetraploids, and in occasional sympatric inland populations. Chloroplast markers resolved distinct genetic groups, related to cytotype and geographically segregated; allopatric hexaploids were distinct from tetraploids, whereas sympatric hexaploids were not. Genome downsizing occurred between cytotypes. Progeny of open-pollinated clones from the contact zone showed that maternal tetraploids rarely produced progeny of other cytotypes, whereas the progeny of maternal hexaploids varied, with frequent pentaploids and aneuploids. The presence of distinctive hexaploid chloroplast types in Ireland, Scottish islands and western mainland Britain indicates that its establishment preceded separation of these land masses by sea-level rise c. 16 000 years BP. This group did not originate from British tetraploids and probably diverged before postglacial invasion from mainland Europe. The combination of cytotype, molecular, contact zone and common garden data shows an overall pattern reflecting postglacial colonization events, now maintained by geographic separation, together with more recent occasional local in situ polyploidisation. Reproductive barriers favour the persistence of the tetraploid to the detriment of the hexaploid. Abstract : Campanula rotundifolia has a distinctive distribution of tetraploid and hexaploid cytotypes in Britain and Ireland. Populations are mostly allopatric, with some exceptions. Chloroplast markers show that allopatric hexaploids are distinct from tetraploids, whereas sympatric hexaploids are not, and that allopatric hexaploids did not originate from British tetraploids. At a simulated contact zone, maternal tetraploids rarely produced progeny of other cytotypes, but maternal hexaploids produced many pentaploids and aneuploids. Present-day distribution reflects postglacial recolonization events, now maintained by geographic separation, together with more recent occasional local in situ polyploidisation. Reproductive barriers favour the persistence of the tetraploid over the hexaploid.